Creating the future of nursing in the post-pandemic world - Colleen Marzilli (Belitung Nursing Journal, 2022)
The COVID-19 pandemic highlighted that nursing cannot go back to its old way of providing care. Care is central to what nurses do and the profession itself, and now is the time for nursing to innovate and reimagine what nursing will look like in the future. From new models of care to technology, nursing has an endless opportunity to innovate the profession. The new model of nursing care must be sustainable and work to maximize nurses while leveraging technology as a tool to help improve quality outcomes. The opportunities are endless, and the time is now to innovate and reimagine nursing and its caring core.